PENERAPAN STRATEGI PEMBELAJARAN KREATIF-PRODUKTIF UNTUK MENINGKATKAN HASIL BELAJAR KETRAMPILAN ANYAMAN BAMBU - Yusnida, Drs. Syafril R, M. Sn, Drs. Suib Awrus, M.Pd (Serupa The Journal of Art Education, 2013)
The objectives of this research is to improve the learning outcomes of woven bamboo Skills class VIII C MTs Tarusan South Coast by implementing creative learning strategies - productive. Classroom action research was conductedby 2 cycles with steps of planning, action, observation and reflection. Data collection tool using teacher observation sheet, observation sheets and student outcomes assessment format belajar.Hasil showed that the pre-cycle average ability students was 66.75. 1 cycle average of 69.5 and the ability of students in the second cycle increased to 76.5. Application of creative-productive learning strategies to improve learning outcomes of students skills bamboo MTs Tarusan significant because the data are processed based on sig of 0.000 <α = 0.05, thenHo is rejected and Ha accepted. Student learning activities in accordance with the results of the research to be active and creative in the application of creativeproductive learning strategies. Kata kunci :hasil belajar, Strategi Pembelajaran Kreatif-Produktif